Credibility and Exposure of Youtube Itechlife for Information Needs Regarding Gadgets on Subscribers - Samatan, Nuriyati; Boestam, Ambia B.; Robingah, Robingah; Febrianto, Bima (International Journal of Advanced Multidisciplinary, 2025)
Research Objective: This research aims to determine the effect of credibility and exposure of Youtube iTechLife on the need for information about gadgets on subscribers. Research methodology: The research method used is quantitative research. The research paradigm is Positivism, sampling determination using probability sampling, through simple random sampling technique. The technique of determining the sample size using the Slovin Formula, with a margin of error of 0.5%, resulted in a sample of 400 respondents on YouTube social media platform users and subscribers to iTechLife. Findings: The results of this research explained that the Credibility and Exposure of Youtube iTechLife toward Information Needs about Gadgets on Subscribers. It can be explained from the results of the Credibility t test which shows t count 5.357> t table 1.965 and the results of the Exposure t test 8.474 >1.965. It can be concluded that Ho1 and Ho2 are rejected and Ha1 and Ha2 are accepted. This means that there is an influence between credibility and exposure to information needs. Also, the coefficient of determination test results showed that iTechLife Youtube Credibility and Exposure had an influence of 46.8% on the need for information about gadgets on subscribers.